The role of technology in acquiring and maintaining English language skills for professional lifelong learning - Athanasiou, Androulla; Burston, Jack (My University, 2023)
The rapid economic and technological developments in a globalised world, dominated by English a lingua franca, have brought about increased competitiveness in the labour market. The role of higher education has become crucial in developing critical competences, e.g. literacy, digital, citizenship, entrepreneurship (European Commission, 2019) and in training undergraduates to deal with the challenges they will face in the labour market as future employees. No matter how good initial training may be at University though, once students graduate, the onus is on them to continue their professional development. If they do not do so, within a year or two they will certainly find themselves out of step with what is happening in their professional domain. Any longer than that and they may find themselves relegated to the sidelines or even out of a job. There is a need, therefore, for future professionals to develop lifelong learning skills from the beginning of their undergraduate studies. The first part of the present paper begins by discussing the importance of lifelong learning for future graduates. It then goes on to explain how English for Specific Purposes courses in higher education can make a double contribution to this endeavor, firstly by providing students with the linguistic competence needed to pursue their professional careers and, secondly, by instilling in students transferable professional lifelong learning habits. In the process, students also become keenly aware of the role of digital technologies as a contributing factor in such courses and in future employees’ lives. The second part of the presentation puts theory into practice with the description of an ESP course in a Cyprus Higher Education State institution that illustrates the structure and activities used, as well as the role of technology in implementing the course, aiming at promoting lifelong learning.
Keywords: Lifelong learning; English for Specific Purposes